HPV‐DNA sperm infection and infertility: from a systematic literature review to a possible clinical management proposal. (1st October 2014) - Foresta, C.; Noventa, M.; De Toni, L.; Gizzo, S.; Garolla, A.
Summary: The objectives of this study were to investigate the implications of human papillomavirus (HPV) sperm infection on male fertility, impairment of sperm parameters, and possible alteration of sperm nuclear status and to identify a possible effective management of infertile men with HPV sperm infection. We employed a systematic review and clinical management proposal at the Centers for Reproductive and Health care for treating infertile male patients with HPV infection. Literature search was carried out in electronic databases in the last two decades. We focused our attention on: (i) HPV sperm prevalence (ii) HPV‐related alteration of sperm parameters; (iii) molecular mechanisms of HPV semen infection and infertility. The main outcome measures were HPV prevalence in infertile male patients and semen parameters. The prevalence of HPV sperm infection ranges between 2 and 31% in men from general population and between 10 and 35.7% in men affected by unexplained infertility. The presence of HPV in semen is associated with an impairment of sperm motility and the presence of anti‐sperm antibodies. The molecular mechanisms underlying impairment of sperm motility apparatus need further evaluations. A greater attention should be applied to assess HPV sperm infection, particularly in men undergoing assisted reproduction techniques cycle for male infertility or sperm banking. It would be useful to perform HPV test and fluorescent in situ hybridization analysis for HPV in semen from these patients both at first admission, to define the possible presence and localization of semen infection, and after 6 months, to assess the possible virus clearance retrieval on normal sperm parameters.